Characterization of patients with ischemic cerebrovascular disease and cognitive impairment. Cienfuegos, 2018 - Beatriz Perdomo Borges; Teresa Rodríguez Rodríguez; Marianela Fonseca Fernández; Isabel Urquiza Pozo; Idalmis Luisa Martínez Serrano; Belkis Rosa Bilaboy Pérez (Medisur)
Foundation: cerebrovascular disease occupies the third place as a cause of death to be overcome only by cardiovascular diseases and cancer. It constitutes the first cause of permanent disability in the adult and the second of dementia. Objective: to characterize patients with cerebrovascular disease and cognitive disorder. Methods: an observational, descriptive, cross-sectional study, carried out in the Neurology Service of the Gustavo Aldereguía Lima Hospital in Cienfuegos, which included 27 patients hospitalized in this center, with cognitive impairment, after the first event of ischemic cerebrovascular disease. The variables were analyzed: sex, age, skin color, schooling, occupation, marital status, origin, toxic habits, personal pathological history, type of cerebrovascular disease, affected brain structure, cognitive impairment (using the minimum Folstein mental state test and the Montreal cognitive assessment test), neuropsychological alterations, depression (using the Yessavage geriatric depression scale). Results: Elderly adults, male sex and white skin color predominated, as well as low level of schooling and singles. The atherothrombotic ischemic event was the most common and the right hemisphere the most affected. There was cognitive impairment in all patients. The risk factors mostly associated with the disease were high blood pressure, diabetes mellitus and smoking. The majority of patients did not suffer depression after cerebral infarction. Conclusions: older, single adults are more likely to suffer strokes. The low educational level may be a factor associated to cognitive impairment after this disease, but depression that does not always manifests deeply.